Enhancement of multijunction solar cell efficiency using a cover layer of Eu3+, Tb3+ and Eu3+/Tb3+ doped GeO2-PbO-Al2O3 glasses as spectral converter of solar radiation - Mattos, G. R.S.; Bordon, C. D.S.; Vilela, O. C.; Gómez-Malagón, L. A.; Kassab, L. R.P. [UNESP] (Elsevier, 2022)
The present study reports the multijunction solar cell efficiency enhancement using a cover layer of GeO2-PbO-Al2O3 glasses single doped with Eu3+ and Tb3+ (with and without Ag nanoparticles (NPs)) and codoped with both of them. We highlight that Al2O3 is a network modifier that promotes the occupation of rare-earth ions in more asymmetric sites, and the change in the coordination environment improves the luminescence that benefits the solar cell efficiency. The influence of the downconversion process and the energy transfer mechanisms between Tb3+ and Eu3+ ions are investigated using different concentrations of Eu2O3 and Tb4O7 in single and codoped samples. Moreover, the plasmonic effects of Ag NPs on the solar cell efficiency increase are also studied and compared with those promoted by different doping concentration to reach the best condition for the multijunction solar cell performance. However, in all cases, it is the contribution of the highest luminescence and considerable transmittance that led to the solar cell best performance. The sample single doped with Eu2O3 promoted an increase of 14%; on the other hand, an increase of 13% was observed for the glass doped with Tb4O7 and with 0.5% of AgNO3. For the case of the codoped samples, solar cell efficiency increase of 10% was reached when the largest Eu2O3 concentration was used.
Keywords: Glasses; Luminescence; Multijunction solar cell; Photovoltaic devices; Rare-earth ions